2016
DOI: 10.1093/mnras/stw478
|View full text |Cite
|
Sign up to set email alerts
|

Effects of galactic disc inclination and resolution on observed GMC properties and Larson's scaling relations

Abstract: With ALMA making it possible to resolve giant molecular clouds (GMCs) in other galaxies, it is becoming necessary to quantify the observational bias on measured GMC properties. Using a hydrodynamical simulation of a barred spiral galaxy, we compared the physical properties of GMCs formed in position-position-position space (PPP) to the observational position-position-velocity space (PPV). We assessed the effect of disc inclination: face-on (PPV face ) and edge-on (PPV edge ), and resolution: 1.5 pc versus 24 p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Several studies of extragalactic GMC populations have also arrived at the same conclusion. However, in theory, it has been suggested that the constant Σ H2 may be a result of the limited surface brightness sensitivity of observations, and in reality, the Σ H2 values of GMCs span at least two orders of magnitude (Kegel 1989;Vázquez-Semadeni et al 1997;Ballesteros-Paredes & Mac Low 2002;Pan et al 2016). …”
Section: Comparison Of Gma Properties Between the Galactic Environmentsmentioning
confidence: 99%
“…Several studies of extragalactic GMC populations have also arrived at the same conclusion. However, in theory, it has been suggested that the constant Σ H2 may be a result of the limited surface brightness sensitivity of observations, and in reality, the Σ H2 values of GMCs span at least two orders of magnitude (Kegel 1989;Vázquez-Semadeni et al 1997;Ballesteros-Paredes & Mac Low 2002;Pan et al 2016). …”
Section: Comparison Of Gma Properties Between the Galactic Environmentsmentioning
confidence: 99%
“…Given that observational studies use a range of cloud definitions, with different clump finding algorithms and using different molecular emission lines, we keep our CO-based definition general, rather than try to match a particular observational study. Pan et al (2016) used a hydrodynamic simulation of a barred spiral galaxy to investigate how the definition of Also, we use projected sizes and compute the velocity dispersion by fitting a single Gaussian component to the CO spectrum. We exclude all clouds that show multiple peaks in their CO spectrum, as they cannot be fit with a single velocity component, and likely consist of multiple clouds that are undergoing mergers.…”
Section: Cloud Scaling Relationsmentioning
confidence: 99%
“…Given that observational studies use a range of cloud definitions, with different clump finding algorithms and using different molecular emission lines, we keep our CO-based definition general, rather than try to match a particular observational study. Pan et al (2016) used a hydrodynamic simulation of a barred spiral galaxy to investigate how the definition of 2016) also explored different definitions of GMCs in PPP or PPV space, based on either H2 or CO, using a high-resolution (3.85 M per SPH particle) resimulation of a section of a spiral galaxy simulation. They found that a PPV-based definition tends to blend clouds that would be physically separated in PPP space, although this effect is less significant if the PPV emission maps have high spatial resolution and high sensitivity.…”
Section: Cloud Scaling Relationsmentioning
confidence: 99%
“…To what extent GMCs are gravitationally bound is still debated. Observation and global simulations suggest that the clouds are probably borderline bound with virial ratios of α ∼ 1-2 (Beaumont et al 2013;Pan et al 2016). However, measuring the virial ratio of a cloud observationally has always been challenging, arising in part from the various assumptions that have to be made (the shape , mass distribution and GMCs being isolated structures) and the results are quite uncertain, with errors of a factor of two.…”
Section: Introductionmentioning
confidence: 99%